ПОЭМАНЫҢ ФОРМАЛЫҚ ҲӘМ ЖАНРЛЫҚ СЫПАТЫ ҲАҚҚЫНДА - Мамбетов, Қ.П. (ILIM hám JÁMIYET, 2017)
The article deals with a literary genre, type, genre form of a poem in Karakalpak study of literature. The author proves from the scientific point of view that a poem is a literary form in Karakalpak poetry.